PERAN TEKNOLOGI INFORMASI UNTUK MENCAPAI KEUNGGULAN KOMPETITIF - ., Erni Widajanti (Universitas Slamet Riyadi, 2008)
ABSTRACT Movement of environmental change very quickly pushes company to immediately to give response to change that happened. This speed aspect represents important matter so that company can reach competitive excellence. To realize speed, many company exploit information technology (IT) is optimal of owned business process. From other side speed, use IT can give appliance which can improve efficacy of company pass the source elementary competitive excellence of company like low expense, very good customer service or management enchain consignment which is superior. Besides IT also give excellence of other competitive to company in the case of information technology assist company develop business which focusing at customer, information technology enable company engineer to repeat business process, information technology enable company become nimble company, information technology make company of virtual, information technology as medium to develop company which can yield knowledge Keywords: information technology, competitive excellence